SEMINAR UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL SABUT PINANG ( Areca catechu L.) TERHADAP Escherichia coli - Asti Pratiwi; Cucu Arum Dwi cahya; Yosi Darmirani (JURNAL PENGMAS KESTRA (JPK), 2021)
Diarrhea one of the major diseases that still being a public health’s problem in Indonesia because of it’s high morbidity and mortality. The common agent of diarrhea is Escherichia coli. One of the many plants that are empirically is Areca catechu L. Coir nut is extracted macerating with ethanol solvent. Extracts obtained by phytochemical screening and this study consisted of 5 treatment groups: extract concentration 30 mg / ml, 60 mg / ml, 90 mg / ml, positive control (Amoxicilin) ​​and negative control (DMSO), with 3 repetitions, antibacterial was performed by the Kirby-Bauer disc diffusion method. Ethanol extract of arco nut contains flavonoid and tannin compounds. Ethanol extract of arco nut has antibacterial activity at concentrations of 30 mg / ml, 60 mg / ml, and 90 mg / ml against Escherichia coli with mean inhibitory zone diameter 14.35 mm, 16.50 mm, 18.17 mm. The result of data analysis using Kruskal-wallis and continued with LSD test (p <0,05) showed that ethanol extract of areca nut had antibacterial activity which was significant to Escherichia coli and the higher concentration, the more area of ​​inhibition zone was produced.